WATER ENVIRONMENT IMPROVEMENT BY INVESTIGATING RIVER WATER QUALITY - Supit, Cindy J. (TEKNO, 2015)
Investigating  river water  quality  is an  important  research  topic in the integrated basin management and  will  providea new  approach to  water  environment improvement. In this study, the observed environment done with the analyzing river water quality. From the  observation,  the  results  show that  the  water  quality of  Kase  River  basin  is generally as good. The conditions in the periods after dam construction indicate that river water quality impairment do exist, but not much and still meet the environmental qualification. The replenishment of Kase River Dam reservoir with the Hokuzan dam reservoir in the basin has less affected to change the water quality along the river due to the good implementation of pollution control in this area. Key words : observed environment, river water quality